Afrodescendentes em São Leopoldo: memória coletiva e processos de identidade - José Ivo Follmann; Adevanir Aparecida Pinheiro (Ciências Sociais Unisinos)
This article focuses on aspects of the methodology used in the process of the research project on "Afro-descendants in São Leopoldo: memory and identity", intending to show some of its most relevant results. We stress the technique called "focus collective hermeneutics", through which we try, by means of workshops with a group of Afro-descendants, to construct a contextualized and pedagogically involving and engaging comprehension, starting from life stories and personal and other reports, collected among the black population of São Leopoldo. The text of the article is developed in different moments, ranging from a brief identification of the limits and methodological insufficiency of the existing studies to the importance of the use of the word "Afro-descendants" to refer to the Afro-Brazilians and some evidences of identity processes, including a brief note about the work developed with Afro-descendants at Unisinos and a discussion of the "why" and "how" of the use of the concept of hermeneutics in accordance with specific aim of the research project carried out.